Home girls : Chicana literary voices - Quintana, Alvina E., 1947- (Temple University Press, 1996)
""Home Girls makes an original, bold, and significant contribution to feminist studies, Chicana/o studies, and literature. Quintana accomplishes what few critics in Chicana/o studies have done: she applies different interpretive paradigms to her reading of Chicana texts, blending ethnography with literary criticism, ideological analysis with semiotics. Her reading of literary texts is rich in texture and detail."--Rosa Linda Fregoso, author of Bronze Screen: Chicana and Chicano Film CultureChicana writers in the United States write to inspire social change, to challenge a patriarchal and homophobic culture, to redefine traditional gender roles, to influence the future. Alvina E. Quintana examines how Chicana writers engage literary convention through fiction, poetry, drama, and autobiography as a means of addressing these motives. Her analysis of the writings of Gloria Anzaldua, Ana Castillo, Denise Chavez, Sandra Cisneros, and Cherrie Moraga addresses a multitude of issues: the social and political forces that influenced the Chicana aesthetic; Chicana efforts to open a dialogue about the limitation of both Anglo-American feminism and Chicano nationalism; experimentations with content and form; the relationship between imaginative writing and self-reflexive ethnography; and performance, domesticity, and sexuality. Employing anthropological, feminist, historical, and literary sources, Quintana explores the continuity found among Chicanas writing across varied genres--a drive to write themselves into being."--Publisher
Keywords: American literature -- Mexican American authors -- History and criticism.; Women and literature -- United States -- History -- 20th century.; American literature -- Women authors -- History and criticism.; Mexican American women -- Intellectual life.; Mexican American women in literature.; Mexican Americans in literature.; Littérature américaine -- Écrivains américains d'origine mexicaine -- Histoire et critique.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Littérature américaine -- Écrivaines -- Histoire et critique.; Américaines d'origine mexicaine -- Vie intellectuelle.; Américaines d'origine mexicaine dans la littérature.; Américains d'origine mexicaine dans la littérature.; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique.; Écrits de femmes américains -- Histoire et critique.; LITERARY CRITICISM -- American -- General.; SOCIAL SCIENCE -- General.; American literature -- Mexican American authors; American literature -- Women authors; Mexican American women in literature; Mexican American women -- Intellectual life; Mexican Americans in literature; Women and literature; United States; Frauenliteratur; Mexicaanse Amerikanen.; Vrouwelijke auteurs.; Chicanos.; Hispanos.; 1900-1999; Criticism, interpretation, etc.; History